PENERAPAN METODE SENI BACA AL-QUR’AN (TILAWATI) UNTUK MENINGKATKAN KEMAMPUAN BACA AL-QUR’AN PESERTA DIDIK KELAS VII DI SMPIT AR-RAHMAH MAKASSAR - Awi Annur; Muhammad Yunus; Bambang Sampurno; Mustamin; Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This Classroom Action Research (CAR) examines the effectiveness of the implementation of the tilawati method in improving the Qur'an reading ability of seventh grade students at SMPIT Ar-rahmah Makassar. This study used CAR through two cycles, involving 33 students as participants. Data were collected through observation, tests, interviews and documentation, then analyzed using percentage and average calculations to measure student activity and student learning outcomes. The implementation of the tilawati method during the two cycles showed a significant increase in students' Qur'an reading ability. In the initial stage (pre-cycle), the average student score was only 66.7 (less than 66.7) with a success rate of 30.30%. After (cycle I), the average value increased to 75.6 (sufficient category), with a success rate of 66.67%, then continued with (cycle II) to strengthen the material that has been taught while encouraging abilities that have not met the KKM standard, the average value increased again to 84.1 (sufficient category) with a success rate of 90.91% (very good category). These results confirm the effectiveness of the tilawati method in improving students' ability to read the Qur'an. Substantial improvement from pre-cycle to cycle II shows the feasibility of this method to be applied in improving the quality of Qur'an learning. Therefore, this study recommends the integration of the tilawati method more broadly into the curriculum of Qur'an and Tahfidz learning for class VII at SMPIT Ar-rahmah Makassar and similar schools. Further research can explore the application of this method at various grade levels in education.